Competing health policies: insurance against universal public systems - Asa Ebba Cristina Laurell (Universidade de São Paulo, 2016)
Objectives: This article analyzes the content and outcome of ongoing health reforms in Latin America: Universal Health Coverage with Health Insurance, and the Universal and Public Health Systems. It aims to compare and contrast the conceptual framework and practice of each and verify their concrete results regarding the guarantee of the right to health and access to required services. It identifies a direct relationship between the development model and the type of reform. The neoclassical-neoliberal model has succeeded in converting health into a field of privatized profits, but has failed to guarantee the right to health and access to services, which has discredited the governments. The reform of the progressive governments has succeeded in expanding access to services and ensuring the right to health, but faces difficulties and tensions related to the permanence of a powerful, private, industrial-insurance medical complex and persistence of the ideologies about medicalized 'good medicine'. Based on these findings, some strategies to strengthen unique and supportive public health systems are proposed.